The Effect of Learning Difficulties on Students' Learning Achievement In Islamic Religious Lessons at Dewi Sri Islam Private SD Perkebunan Tanjung Kasau, Sei Suka District, Batu Bara Regency - Nova Erawati Sidabalok (IJCS: International Journal of Community Service, 2022)
This study discusses learning difficulties and their effect on student achievement in Islamic subjects at Dewi Sri Private Islamic Elementary School, Tanjung Kasau Plantation, Sei Suka District, Batu Bara Regency . The results of the study indicate that learning difficulties affect the learning achievement of Islamic Religious Education students at Dewi Sri Islamic Private Elementary School at Tanjung Kasau Plantation, Sei Suka District, Batu Bara Regency. This is shown from the simultaneous test of learning difficulties in obtaining F count 5.468 with a significance of 0.023. Because the significance value of learning difficulties < 0.05, it can be concluded that simultaneously learning difficulties affect student achievement in Islamic religious subjects at Dewi Sri Islamic Private Elementary School, Tanjung Kasau Plantation, Sei Suka District, Batu Bara Regency.